Ataxia, peripheral neuropathy, and anti-gliadin antibody. Guilt by association?. Issue 11 (14th October 2005) - Lock, R J; Pengiran Tengah, D S N A; Unsworth, D J; Ward, J J; Wills, A J
Abstract : Some authors contend that patients with idiopathic neurological disease who are also anti-gliadin antibody seropositive are gluten sensitive. However, anti-gliadin antibodies lack disease specificity being found in 10% of healthy blood donors. We report a study comparing anti-gliadin antibody with other food antibodies in patients with idiopathic ataxia (20), hereditary ataxias (seven), or idiopathic peripheral neuropathy (32). Patients were HLA typed. IgA anti-tissue transglutaminase antibodies (tTG) were measured. No case was positive for IgA anti-tTG making occult coeliac disease unlikely. HLA DQ2 and HLA DQ8 were found distributed equally across all patient groups and unrelated to gliadin antibody status. HLA DQ2 expressing, anti-gliadin antibody positive cases (so called "gluten ataxia") were rare in our clinics (four cases in 2 years from a population of 2 million). We conclude that coeliac disease per se is not commonly associated with either idiopathic ataxia or idiopathic peripheral neuropathy. Our study also casts doubt on the nosological status of "gluten ataxia" as a discreet disease entity. All food antibodies tested, particularly IgG, were a common finding in both ataxia and peripheral neuropathy groups. No particular food antibody was associated with any patient group. Food antibodies were equally common in hereditary ataxias. We conclude they are a non-specific finding.